2015
DOI: 10.1017/s0007114515004547
|View full text |Cite
|
Sign up to set email alerts
|

Changes in milk composition in obese rats consuming a high-fat diet

Abstract: Maternal obesity programmes offspring development. We addressed maternal obesity effects induced by high-fat diets on maternal mammary gland (MG) structure and function and offspring brain, liver and fat outcomes. Mothers were fed control (C, n 5) or obesogenic (MO, n 5) diet from the time they were weaned through pregnancy beginning at 120 d, through lactation. At offspring postnatal day (PND) 20, milk leptin and nutrients were determined. At the end of lactation, maternal liver and MG fatty acid profile were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 44 publications
9
63
0
3
Order By: Relevance
“…Confirming this hypothesis, studies have shown that the quality of maternal dietary lipids consumed during lactation is correlated to the nutritional profile secreted of milk (Bautista et al, 2016;Oosting et al, 2015). According to Purcell et al (2011), on the 10th day, the milk of rats fed with a high fat diet becomes more caloric and high in fat.…”
Section: Discussionmentioning
confidence: 90%
“…Confirming this hypothesis, studies have shown that the quality of maternal dietary lipids consumed during lactation is correlated to the nutritional profile secreted of milk (Bautista et al, 2016;Oosting et al, 2015). According to Purcell et al (2011), on the 10th day, the milk of rats fed with a high fat diet becomes more caloric and high in fat.…”
Section: Discussionmentioning
confidence: 90%
“…Maternal obesity is known to alter milk fatty acid composition, along with decreasing water and carbohydrate content in milk and increasing fat [44]. De novo fatty acid synthesis has been shown to be impaired by administration of a HFD in the mouse mammary gland through inhibition of acetyl-CoA carboxylase [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same group observed an increased Elovl2 expression in adipose tissue within the first half of the lactation period (36), suggesting improved mobilization of DHA from internal sources. There are also reports regarding low levels of Elovl2 mRNA and protein in placenta and in mammary glands during lactation (35)(36)(37)(38). Several studies have implied that maternal DHA supplementation may rescue DHA depletion during pregnancy and lactation and lead to a successful supply of DHA to the offspring (30,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%